Are experiences of psychosis associated with unhelpful metacognitive coping strategies? A systematic review of the evidence. (23rd August 2017) - Sellers, Rachel; Wells, Adrian; Morrison, Anthony P.
Abstract : This review investigated whether unhelpful metacognitive coping strategies, such as attentional biases, worry, rumination, and thought control, are associated with experiences of psychosis. These processes, known collectively as the Cognitive Attentional Syndrome (CAS), form a central tenet of the Self‐Regulatory Executive Function model. Three research questions based on assumptions underlying the CAS were addressed. It was predicted that processes of (a) self‐focused processing, (b) negative perseverative thinking (worry and rumination), and (c) counterproductive thought control would be associated with experiences of psychosis. A comprehensive search of the literature identified 51 eligible studies: 17 investigated self‐focused attention, 25 investigated perseverative processing (worry: n  = 18; rumination: n  = 10), and 9 investigated thought control strategies. Findings indicated that unhelpful metacognitive coping strategies associated with the CAS are related to experiences of psychosis and appear to share important relationships with distress. Implications for future research and clinical practice are discussed.